Faktor-Faktor yang Berhubungan dengan Perilaku Keluarga dalam Pencegahan Penularan Tuberkulosis di Puskesmas Kenali Besar Kota Jambi Tahun 2025 - Ainun Nazmi Hasibuan; Helmi Suryani Nasution; Ashar Nuzulul Putra; Muhammad Syukri (JUKEJ : Jurnal Kesehatan Jompa, 2026)
Tuberculosis remains a major public health problem in Indonesia, including in Jambi City. The risk of tuberculosis transmission is highest among household contacts; therefore, the behavior of family members of TB patients plays an important role in preventing transmission. This study aimed to analyze the factors associated with family behavior in preventing tuberculosis transmission in the working area of the Kenali Besar Public Health Center, Alam Barajo District, Jambi City, in 2025. The study population consisted of all family members living in the same household as tuberculosis patients, with a total sample of 88 respondents selected using a total sampling technique. The independent variables included age, sex, education level, occupation, income, knowledge, and attitude, while the dependent variable was tuberculosis transmission prevention behavior. Data were collected using a structured questionnaire and analyzed using univariate and bivariate analyses with a 95% level of significance. The results showed that education level, income, knowledge, and attitude were significantly associated with family behavior in preventing tuberculosis transmission.